Manga Shakespeare. As you like it - Kutsuwada, Chie; Appignanesi, Richard; Shakespeare, William, 1564-1616 (Appignanesi, Richard. Manga Shakespeare., 2009)
Banished to the Forest of Arden, Rosalind, disguised as a boy, reunites with true love Orlando. Presented in comic book format.